How effective is the community medicine posting to cultivate teamwork, leadership and professionalism among medical students in Universiti Putra Malaysia?: enhancing best practice of future doctors - Minhat, Halimatus Sakdiah; Mat Din, Hazwan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: This study aimed to assess the effectiveness of the Community Medicine Posting to instilling and cultivating teamwork, leadership and professionalism among the medical students in Universiti Putra Malaysia. Methods: Self-administered questionnaire consisted of sociodemographic characteristics, professionalism, teamwork and leadership sections was distributed to the year four medical students before and after the Community Medicine Posting. The posting lasted for 6 weeks and served as an intervention for the purpose of this study. Results: A total of 107 of medical students were involved with mean age of 22.64 ± 0.63 years old. The mean score for professionalism and leadership were significantly (p<0.001) increased following the posting, with leadership had the highest mean difference of 10.12. Conclusion: The study confirmed the effectiveness of the Community Medicine Posting to cultivate leadership and professionalism skills among the medical students, and surprisingly not effective towards teamwork. Professionalism and leadership are two essential skills towards medical best practices.